Comparative Evaluation of a Modified Laryngoscope Blade for Apneic Oxygenation during Airway Management of Pediatric Patients: A Prospective, Randomized Clinical Trial - Jitendra Pandey; Prakash K. Dubey; Swati Singh (Bali Journal of Anesthesiology)
Background: Pediatric patients are prone to oxygen desaturation during the induction of general anesthesia. The effectiveness of apneic oxygenation in preventing adverse respiratory events necessitates the use of various strategies to increase safe apneic time. The study aimed to compare the efficacy of the modified Miller’s laryngoscope with oxygen insufflation with that of the normal Miller’s laryngoscope. Patients and Methods: One hundred and sixty children (age = 1–10 years) undergoing general anesthesia with endotracheal intubation for surgery were recruited and randomly assigned to one of the two groups: oxygenation group (intubation performed using laryngoscopy performed with modified Miller’s blade) or control group (classical Miller blade). The primary outcome measure was successful and uneventful intubation. Secondary outcomes included the need for multiple attempts at intubation and hemodynamic parameters throughout the study period. Results: The median (interquartile range) time for intubation on the first attempt was 58 s (50–108 s) in the oxygenation group compared to 55 s (48–106 s) in the control group (P = 0.071). However, the overall lowest oxygen saturation (SpO2) level observed within 6 min was significantly lower in the control group as compared to the oxygenation group (P < 0.001). The oxygenation group observed SpO2 levels of 100% in 75% of patients, whereas the control group observed them in 52.5% (P = 0.003). Conclusion: Using a modified Miller’s laryngoscope for apneic oxygen insufflation effectively extended the safe apneic time, while maintaining hemodynamic stability during pediatric intubations.